IMPLEMENTASI POSITIF DEVIANCE (PENYIMPANGAN POSITIF) DALAM PEMBERDAYAAN PERPUSTAKAAN DI DINAS KEARSIPAN DAN PERPUSTAKAAN DAERAH KABUPATEN WONOSOBO - Zulaikha, Sri Rohyanti (Thaqafiyyat : Jurnal Bahasa, Peradaban dan Informasi Islam, 2018)
This article discusses the implementation of Positive Deviance in the Library Empowerment in the Office of Regional Archives and Library. The purpose of this study is to explain the action carried out by the Regional Library towards the development of its library through the practice of Positive Deviance. The method employed in this research is descriptive qualitative using data analysis of Miles and Huberman. The research finds that the Office of Regional Library and Archives in Wonosobo developed its library by some innovations in its services. The Regional Library also produces various achievements and innovations as a result of the strategic phases of library development in applying the concept of Positive Deviance. Finally, this study recommends that the implementation of Positive Deviance could also be implemented to the Village Libraries in the Regency of Wonosobo by empowering the advantages of local wisdom in each Village Library